The Effectiveness of Silane and Siloxane Treatments on the Superhydrophobicity and Icephobicity of Concrete Surfaces - (:unkn) unknown (My University, 2013)
Icy roads lead to treacherous driving conditions in regions of the U.S., leading to over 450 fatalities per year. De-icing chemicals, such as road salt, leave much to be desired. In this report, commercially available silane, siloxane, and related materials were evaluated as solutions, simple emulsions, and complex emulsions with incorporated particulates, for their effectiveness as superhydrophobic treatments. Through the development and use of a basic impact test, the ease of ice removal (icephobicity) was examined as an application of the targeted superhydrophobicity. A general correlation was found between icephobicity and hydrophobicity, with the amount of ice removed on impact increasing with increasing contact angle. However, the correlation was poor in the high performance region (high contact angle and high ice removal.) Polymethylhydrogensiloxane was a top performer and was more effective when used as a "shell" type emulsion with silica fume particulates. An aqueous sodium methyl siliconate solution showed good performance for ice loss and contact angle, as did a commercial proprietary emulsion using a diethoxyoctylsilyl trimethylsilyl ester of silicic acid. These materials have sterically available functional groups that can react or associate with the concrete surface and are potentially film-forming. Materials with less reactive functional groups and a lower propensity to film-form did not perform as well.
Keywords: Cement; Hydrophobic; Icephobic; Mortar; Overhydrophobic; Superhydrophobic